Tuberculosis Patient Adherence to Treatment and Transmission to Home Contact Family Members - Ernawaty Siagian (Universitas Padjadjaran, 2019)
Tuberculosis is a contagious disease that remains a health problem worldwide. Treatment of tuberculosis is one of the main strategies in controlling tuberculosis because it can break the transmission chain, especially in families of household contacts where transmission is twice as risky as casual or unfamiliar contact. The purpose of this study was to analyze secondary data on patient adherence to pulmonary tuberculosis treatment sessions and transmission to household contact families in 2016-2017 at a private hospital in Indonesia. This research used a correlative descriptive design with Secondary Data Analysis (ADS) approach using existing data as primary data that is TB 06 and TB 09 data, TB 01 (medical card TB PKM). The population in this research was based on the report of patient data of TB DOTS year 2016-2017 with 60 TB patients. The statistical analysis used was Pearson’s r. The result of the research showed that the patient’s adherence of pulmonary tuberculosis to treatment sessions. [D1] The value of adherence was seen from all respondents of tuberculosis patients which coming to the referral clinic according to the TB 06, and TB 09. As well as the patient’s record card at the referral clinic showed all the respondents routinely took the anti tuberculosis medication and completed the treatment as recommended by the doctor. Investigation based on 60 respondents, there is 23.3% or 14 people diagnosed based on sputums, while remaining 46 people or 76.7% [D2] based on radiology results. Identification of household contact families members found positive sputum smear examination of 5 people (8.3%) and found to be undergoing tuberculosis treatment as many as 4 people (6.7%).The results of this study found a relationship between tuberculosis patient adherence to treatment sessions and transmission to household contact family with P value 0.001 (<0.05) with a moderate correlation (r) = 0.378%. For further [D3] treatment, the nurse includes TB 06 and TB 09 sheets for follow up treatment at the public health service center. [D1]Edit the sentence [D2]Please use the correct sentence to explains this data [D3]Are tb patients hospitalized? Did you mean nursing care at home>